Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama - Arce-Pérez, Roberto; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2017)
Psephenops bifidus sp. nov. and Psephenops triangularis sp. nov. are described, based on specimens collected from Altos del María, Chame District, Panama, rising the total number of species assigned to this genus in the Mesoamerican region to twelve. Both species can be separated easily from other known Psephenops species by a combination of several features, but mainly by the prosternal process and the lateral projections of penis respectively.